2013
DOI: 10.1002/chem.201301586
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Luminescent Cyclometalated Platinum(II) Complexes of 1,3‐Bis‐Hetero‐Azolylbenzenes with Tunable Color for Applications in Organic Light‐Emitting Devices through Extension of π Conjugation by Variation of the Heteroatom

Abstract: A series of luminescent cyclometalated platinum(II) complexes of N^C^N ligands [N^C^N=2,6-bis(benzoxazol-2'-yl)benzene (bzoxb), 2,6-bis(benzothiazol-2'-yl)benzene (bzthb), and 2,6-bis(N-alkylnaphthoimidazol-2'-yl)benzene (naphimb)] has been synthesized and characterized. Two of the platinum(II) complexes have been structurally characterized by X-ray crystallography. Their electrochemical, electronic absorption, and luminescence properties have been investigated. In dichloromethane solution at room temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 75 publications
6
42
0
Order By: Relevance
“…It has also been demonstrated that the electronic nature (withdrawing/donating) of the substituent attached to the aryl ring as well as the alkynyl ligand produce changes in the excited states, thereby modifying the emission colour, purity and quantum yield. 31 In addition to the geometric distortion-dependent PL properties in solution, cyclometallated Pt(II) complexes display solid-statedependent emission due to the different extent of intermolecular interaction such as metallophilic and other non-covalent interactions. Unarguably, the introduction of alkynyl units enhances the propensity of such interactions and increases the crystallinity of the material, leading to synergistic modulation of PL properties.…”
Section: Platinum(ii) Alkynyl Complexes With C^n^n Pincer Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that the electronic nature (withdrawing/donating) of the substituent attached to the aryl ring as well as the alkynyl ligand produce changes in the excited states, thereby modifying the emission colour, purity and quantum yield. 31 In addition to the geometric distortion-dependent PL properties in solution, cyclometallated Pt(II) complexes display solid-statedependent emission due to the different extent of intermolecular interaction such as metallophilic and other non-covalent interactions. Unarguably, the introduction of alkynyl units enhances the propensity of such interactions and increases the crystallinity of the material, leading to synergistic modulation of PL properties.…”
Section: Platinum(ii) Alkynyl Complexes With C^n^n Pincer Ligandsmentioning
confidence: 99%
“…Carbazole and its derivatives exhibit interesting emission properties and act as triplet emitters due to their rigidity and electron donor properties. Yam et al 31 found that the absorption and emission properties of complexes bearing 9-(prop-2-ynyl)-9Hcarbazole as the auxiliary ligand is governed by substituents attached to the central arene ring (p-butoxy, butyl or H) as well as the heteroatoms (N, O, S) present in the cyclometallating core (Chart 5). Electrochemical results suggested that the inductive effect of s-donating substituents at the 5-position of the aryl ring of the N^C^N ligand destabilizes the lowest unoccupied molecular orbital (LUMO).…”
Section: Platinum(ii) Alkynyl Complexes With C^n^n Pincer Ligandsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30] These systems have a strong propensity to aggregate in solution and in the solid state via Pt•••Pt and/or other secondary forces, as recently shown for various classes of complexes in a comprehensive review by Yam and co-workers. 31 Among them, the self-assembly features of hydrophobic Pt(II) complexes with acetylide, [32][33][34][35][36] bidentate, [37][38][39] tridentate N-donor, [40][41][42] and cyclometalating ligands [43][44][45] are relatively well understood. 31 In contrast, their hydrophobic counterparts featuring non-chelating ligands and, in particular, bis(pyridyl) Pt(II) complexes have been limited to liquid crystalline materials [46][47][48] and hydrogen-bonded metallogelators.…”
Section: Introductionmentioning
confidence: 99%
“…Square-planar platinum(II) complexes have proven to be strong phosphorescent compounds, and have been extensively explored with respect to a broad field of promising applications, such as chemosensors, [1][2][3][4][5][6] non-linear optical (NLO) materials, [7][8][9] photocatalysts, [10][11][12][13][14] optical power limiting materials (OPL), 15 photovoltaic devices, 16,17 and organic light emitting devices (OLEDs). [18][19][20][21][22][23][24][25] Concerning the field of OLED technology especially blue emitting compounds are required to develop full-color displays and efficient lighting devices. Cyclometalated platinum(II) complexes represent a promising class for this purpose, as shown from several reports.…”
Section: Introductionmentioning
confidence: 99%